Staff perspectives on poor mental health in secondary school students: an increasing problem handled with insufficient resources - Svensson, Åsa; Warne, Maria (Frontiers in Public Health, 2024)
Introduction An increasing number of schools are recognizing the importance of addressing students' mental health based on the association with educational outcomes and long-term health. The school organization and the members of the school staff play important but, in several ways, challenging roles in this work. The purpose of this study was to explore views of staff from schools and school health services on mental ill health among students and their own role in detecting and managing it. Methods A qualitative study was conducted in a sparsely populated municipality in northern Sweden. In total, 40 participants from three secondary schools and the school health services participated either in focus groups or individual interviews. Participants were teachers, assistants, school nurses, school counselors and psychologists. Data were analyzed using thematic analysis. Results The analysis revealed the main theme Student mental ill health: an increasing problem handled with insufficient resources and two subthemes, i.e., Uncertainty in interpreting students' signs of mental ill health and the need to clarify roles and establish a supportive organization. Conclusions It was concluded that school staff were uncertain regarding how to interpret signs of mental ill health among students and required better knowledge and more resources to help students with mental ill health. A clearer organization and consensus regarding support for students with mental ill health were also necessary in light of the division of responsibilities between school staff and the school health services.